The Influence of Culinary Diversity and Tourism Events on Tourist Expenditures (Study in Central Lombok Regency with Destination Image as Intervening Variable) - Dewi, Irra Chrisyanti; Sulistyo, Joko (International Journal of Business, Law, and Education, 2024)
This research investigates the interplay between culinary diversity, tourism events, destination image, and tourist expenditures in Central Lombok Regency, Indonesia. A quantitative approach utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to analyze data gathered from domestic and international tourists. Hypothesis testing revealed significant positive relationships between culinary diversity and tourist expenditures, tourism events and tourist expenditures, culinary diversity and destination image, tourism events and destination image, as well as indirect effects through destination image on tourist expenditures. The result highlights the economic importance of diverse culinary experiences and engaging events in driving tourism revenue, shaping destination image perceptions, and influencing tourists' spending behaviors. The study underscores the need for integrated destination management strategies to leverage Central Lombok's cultural and gastronomic assets for sustainable tourism development.